Perinatal mental health in India: protocol for a validation and cohort study. (8th October 2021) - Fellmeth, G; Kishore, M T; Verma, A; Desai, G; Bharti, O; Kanwar, P; Singh, S; Thippeswamy, H; Chandra, P S; Kurinczuk, J J; Nair, M; Alderdice, F
ABSTRACT: Background: Common mental disorders (CMD) are among the largest contributors to global maternal morbidity and mortality. Although research on perinatal mental health in India has grown in recent years, important evidence gaps remain, especially regarding CMD. Our study aims to improve understanding of CMD among perinatal and non-perinatal women of reproductive age across two settings in India: Bangalore (Karnataka) and Tanda (Himachal Pradesh). Methods: The study is embedded within the Maternal and Perinatal Health Research Collaboration India (MaatHRI). This mixed-methods observational study comprises three consecutive phases: (i) focus group discussions and individual interviews to explore women's knowledge and seek feedback on CMD screening tools; (ii) validation of CMD screening tools; and (iii) prospective cohort study to identify CMD incidence, prevalence and risk factors among perinatal and non-perinatal women. Results of the three phases will be analyzed using inductive thematic analysis, psychometric analysis and multivariable regression analysis, respectively. Conclusion: Improving understanding, detection and management of CMD among women is key to improving women's health and promoting gender equality. This study will provide evidence of CMD screening tools for perinatal and non-perinatal women in two diverse Indian settings, produce data on CMD prevalence, incidence and risk factors and enhance understanding of the specific contribution of the perinatal state to CMD.